2017
DOI: 10.1088/1361-6560/aa8134
|View full text |Cite
|
Sign up to set email alerts
|

Fred: a GPU-accelerated fast-Monte Carlo code for rapid treatment plan recalculation in ion beam therapy

Abstract: Ion beam therapy is a rapidly growing technique for tumor radiation therapy. Ions allow for a high dose deposition in the tumor region, while sparing the surrounding healthy tissue. For this reason, the highest possible accuracy in the calculation of dose and its spatial distribution is required in treatment planning. On one hand, commonly used treatment planning software solutions adopt a simplified beam-body interaction model by remapping pre-calculated dose distributions into a 3D water-equivalent represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 37 publications
1
71
0
Order By: Relevance
“…Measured and simulated FSFs in this study agreed well with three other studies 4,5,18 for the highest energy, but differences up to 1% were observed for the largest field sizes compared to two other studies 3,11 (see Fig. S3).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Measured and simulated FSFs in this study agreed well with three other studies 4,5,18 for the highest energy, but differences up to 1% were observed for the largest field sizes compared to two other studies 3,11 (see Fig. S3).…”
Section: Discussionsupporting
confidence: 89%
“…In that study, six out of seven planes in an anthropomorphic phantom passed a 90% Gamma index analysis criterion (3%/3 mm) for their MC simulations compared to film measurements, whereas only three out of seven passed using the PB algorithm. Speed optimized MC algorithms dedicated for routine clinical use are usually benchmarked against general purpose MC particle transport algorithms such as FLUKA and Geant4 . The latter are traditionally used during commissioning phase to support basic beam data generation required for treatment planning systems (TPSs) allowing to reduce time consuming measurements …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter means that the next generation treatment planning systems should incorporate the handling of the uncertainties related with the beam delivery, patient positions, RBE models, etc. GPU‐based TPS could represent a promising solution of these problems . The speed of dose and RBE computations is also a key prerequisite for advanced treatment planning tools such as multicriteria and automatic optimization, and robust optimization, where linearity in dose addition is frequently exploited to speed up calculations; however, this linearity is not given for RBE‐weighted particle dose distributions.…”
Section: Light Ionsmentioning
confidence: 99%
“…GPU-based TPS could represent a promising solution of these problems. [94][95][96] The speed of dose and RBE computations is also a key prerequisite for advanced treatment planning tools such as multicriteria and automatic optimization, and robust optimization, where linearity in dose addition is frequently exploited to speed up calculations; however, this linearity is not given for RBE-weighted particle dose distributions.…”
Section: Light Ionsmentioning
confidence: 99%